Measurement of external rotation of the shoulder in patients with obstetric brachial plexus palsy - Blaauw, Gerhard; Muhlig, Robert S (Journal of Brachial Plexus and Peripheral Nerve Injury, 2012)
A discussion is presented concerning scoring while assessing shoulder function. Divergence in observation and in interpretation of what is observed may give rise to serious disagreement about indications for surgery. Agreement regarding starting points of measurement is essential. One must realize that the number of degrees, obtained using a scoring system, may not reflect the real amount of motion per se, it may solely indicate the limit of the motion in relation to the neutral zero point of the measurement. This realization may improve the justification of and the indication for surgical treatment.It is worthy of mention that this paper deals in particular with active external rotation. Indications for secondary surgery to prevent gleno-humeral deformation if passive external rotation is diminishing progressively, is a separate topic. We wish to point out that the insidious problem of fixed deformity, even to a minor degree, will contribute to the problem of loss of active functional movement.